Are we preparing future doctors to deal with emotionally challenging situations?: analysis of a medical curriculum - Baessler, Franziska; Zafar, Ali; Schweizer-Schubert, Sophie; Ciprianidis, Anja; Sander, Anja; Erdmann, Stella; Bartolovic, Marina; Ditzen, Beate; Roesch-Ely, Daniela; Nikendei, Christoph; Schultz, Jobst-Hendrik (Patient education and counseling, 2019)
Objective - Skilful communication by doctors is necessary for healthcare delivery during emotionally challenging situations. This study analyses a medical curriculum for the frequency and intensity of teaching content on communication in emotionally challenging situations. - Methods - A questionnaire with 31 questions (“EmotCog31”) was used to evaluate teaching sessions at 17 departments of a medical school for one semester. - Results - Teaching content on communication in emotionally challenging situations was observed in 62 of 724 (∼nine percent) teaching sessions. Fifty-six percent of these sessions were within psychosocial specialisations. Lecturers used mental diseases as teaching topics four times more than somatic diseases. Forty-two percent of the 62 sessions were large-group while fifty-eight percent were small-group, interactive sessions. Clinical examples were used in sixty-nine percent of these sessions. Eighty-one percent of the handouts provided and sixty-six percent of simulated patient scenarios used were rated as helpful. Two-thirds of teaching sessions were rated positively when they included practical context. - Conclusion - There was a considerable lack of teaching on communication skills in an emotional context. Teaching was limited to psychosocial specialties, reducing the impact of available knowledge for other medical specialties. - Practice Implications - More interactive, practically oriented teaching methods are useful for teaching emotional communication skills.
Gesehen am 19.06.2019